Validitas Modul Elektronik “Pembelahan Sel” Berbasis Keterampilan Berpikir Kritis - Nadia Astuti; Kaspul Kaspul; Maulana Khalid Riefani (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
Along with the rapid development of the times, the use of technology is widely used by students in schools. The use of technology-based teaching aids will make teaching and learning activities more fun, easy, and efficient. One of the teaching aids is teaching materials. Teaching materials that are easy, practical, and close to life will make it easier for students to understand the lesson. Cell division material is still considered a difficult learning material. This is because the characteristics of the object are indeed difficult to be presented in real to students. Therefore, research and development on teaching materials are carried out in the form of cell division material modules for class XII SMA based on critical thinking skills. This research and development aim to describe the validity of the e-module material for class XII high school cells based on critical thinking skills. This type of research is research and development with a 4D model. Aspects of validity include aspects of compatibility and participation. The research data were analyzed descriptively in categories. The results showed that the e-module developed was in the very appropriate category with a value of 3.83, which means that this e-module was in accordance with the objectives of learning Biology at SMA 4 Banjarmasin and received a feasibility score of 3.93 in the very feasible category, which means that the module is technically very feasible to be used as a source of learning Biology.